All-fiber frequency shifted self-mixing interferometry for slow flow measurements. (April 2023) - Liu, Keyan; Zhao, Yunkun; Zhang, Lei; Li, Ruifeng; Hu, Jun; Du, Zhengting; Hu, Zhijia; Yu, Qi; Li, Hongtao; Yu, Benli; Lu, Liang
Highlights: A new method is presented to measure slow flow velocity based on self-mixing effect. Flow velocity is obtained by the frequency difference from asymmetric power spectrum. This scheme can be applied for direction determination of the flow velocity. The maximum achievable Doppler shift within the pipe is measured as low as 15.37 Hz. Abstract: In this study, an all-fiber structure self-mixing sensor using a distributed feedback Bragg (DFB) fiber laser as the light source is proposed to measure flow velocity. In pursuit of slower flow velocity, the external cavity frequency-shifting optical technique is introduced into the optical sensing system to effectively avoid complex noises existing in the low-frequency region. Furthermore, the additional bonus is that the identification of the velocity direction can be obtained by the asymmetric shape near the feedback frequency shift on the spectrum. At the same time, a suitable solution is developed for extraction of the characteristic feature parameters from the asymmetrical spectrum of the flow velocity signal. It was demonstrated the actual conformity of the measurement results by means of this new approach of data processing. According to the practical experimental measurements, the maximum measurable Doppler shift concerning the slow fluid can be obtained as low as 15.37 Hz. This indicates that the designed all-fiber laser self-mixing flow velocity meter can be prospectively extended to slow fluid measurement associated with the related sensing and medical applications.